Management Performance Improvement Strategy School at SMK Negeri 2 Kayuagung - Budiman, Indra; Fitria, Happy; Ahyani, Nur (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe strategies for improving school management performance at SMK Negeri 2 Kayuagung. Data collection tools using interviews, documentation, observation and literature review. Data analysis used descriptive qualitative analysis with research stages referring to Miles and Huberman’s theory, namely data collection, data reduction, data presentation, drawing conclusions. The results of the study stated that the principal’s strategy at SMK Negeri 2 Kayuagung in improving management performance through the planning sector, the organizing sector, the implementation sector and the supervision sector at SMK Negeri 2 Kayuagung. The obstacles faced in improving school management performance are in the implementation sector of improving the quality of learning and increasing teacher competence at SMK Negeri 2 Kayuagung. Solutions to some of the obstacles include 1) carrying out continuous coaching and training of teachers, supervising, evaluating and providing directions for improvement.